Consider a continuous and differentiable function $f$ with a maximum point at $x=c$. I want to show that

$$\lim_{h \to 0-}\frac{f(c+h) - f(c)}{h} \geq 0$$

$$\lim_{h \to 0+}\frac{f(c+h) - f(c)}{h} \leq 0$$

must be true. But when I tried to set up the typical epsilon-delta formulation I very quickly got stuck.

This is what I tried, for the left-hand limit:

Since $c$ is a maximum we have $f(c) \geq f(c+h)$ for all $h$. Then:

$$\lim_{h \to 0-}\frac{f(c+h) - f(c)}{h} \geq 0 \iff \\\forall \epsilon>0, \exists \delta>0 : \forall h, \forall k \geq 0, 0 < 0-h < \delta \implies \left|\frac{f(c+h) - f(c)}{h}-k\right| < \epsilon$$

I don't even know if this is right but it was how I tried to structure the limit definition to accommodate a left-handed limit being $\leq 0$. But even in this form I wasn't able to prove it.

How does one prove these inequalities?

  • $\begingroup$ Can you show that if $g(h) \geq 0$ for all $h$, and $\lim_{h\to 0} g(h)$ exists, then $\lim_{h\to 0} g(h) \geq 0$? $\endgroup$ – Matthew Leingang Mar 20 '18 at 17:17

Let $L=\lim_{h\rightarrow 0^{-}}\dfrac{f(c+h)-f(c)}{h}$, we are to show that $L\geq 0$.

Given $\epsilon>0$, there is a $\delta>0$, for $-\delta<h<0$, then $\left|\dfrac{f(c+h)-f(c)}{h}-L\right|<\epsilon$, then $L-\dfrac{f(c+h)-f(c)}{h}>-\epsilon$, then $L>\dfrac{f(c+h)-f(c)}{h}-\epsilon$.

Since $f$ has maximum at $x=c$, then $f(c+h)\leq f(c)$, so $f(c+h)-f(c)\leq 0$. Since $h<0$, so $\dfrac{f(c+h)-f(c)}{h}\geq 0$, so $L>-\epsilon$. Since this is true for all $\epsilon>0$, we have $L\geq 0$. If not, just put $\epsilon=-L$, then we end up with $L>-(-L)=L$, a contradiction.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.